The Potential Use of the Epigenetic Remodeler LIKE HETEROCHROMATIN PROTEIN 1 (LHP1) as a Tool for Crop Improvement - Mansilla, Natanael (2023)
The vast diversity of traits exhibited by horticultural crops largely depends upon variation in gene expression regulation. The uppermost layer of gene expression regulation is chromatin compaction. In plants, the LIKE HETEROCHROMATIN PROTEIN 1 (LHP1) is a member of the Polycomb Repressive Complex 1 (PRC1) that controls the spreading of the H3K27me3 mark throughout the genome to regulate gene expression. Much of the epigenetic control exerted by LHP1 has been deeply explored on the model species Arabidopsis thaliana. Recent advances in melon, tomato, and soybean highlight the relevance of LHP1 in controlling the development and physiology of a plethora of traits in crops. However, whether LHP1 exerts its diverse roles through similar mechanisms and through modulating the same target genes has been overlooked. In this review, we gather a wealth of knowledge about the LHP1 mode of action, which involves a tight connection with histone marks and long noncoding RNAs to modulate gene expression. Strikingly, we found that LHP1 may be linked to H3K27me3 regulation across the plant lineage, yet, through epigenetic regulation of a distinct set of target genes. This is supported by subtle differences in subcellular LHP1 localization between species found here. In addition, we summarize the variety of developmental outputs modulated by LHP1 across land plants pinpointing its importance for plant breeding. Hence, LHP1 has probably been co-opted in different lineages to modulate diverse traits contributing to crop diversification.